Malaysia National Annex to MS EN 1998-1: 2015, Eurocode 8: Design of structures for earthquake resistance - Part 1: General rules, seismic actions and rules for buildings - Raudhah, Ahmadi; Abdul Razak, Abdul Karim; Norazzlina, M.Sa'don (DEPARTMENT OF STANDARDS MALAYSIA, 2017)
The Malaysia National Annex was developed by the Technical Committee on Earthquake under the authority of the Industry Standards Committee on Building, Construction and Civil Engineering. Development of this national annex was carried out by The Institution of Engineers, Malaysia which is the Standards-Writing Organisation (SWO) appointed by SIRIM Berhad to develop standards for earthquake. This standard is based on the National Annex to BS EN 1998-1:2004, Eurocode 8: Design of structures for earthquake resistance - Part 1: General rules, seismic actions and rules for buildings and is implemented with the permission of the British Standards Publishing Ltd.